Predicting Acdemic Success among Student-Athletes - Cone, Alison E.; Rosenbaum, Jill L. (My University, 1990)
This paper examined various measures that may be useful in predicting graduation among student-athletes. Rather than simply focus on the most·commonly used measures (SAT scores and high school grade point average) four groups of variables were utilized: demographics, high school prepara-tion, university-related variables, and athletic participation fpr 105 student records at one institution. Both bivariate and multivariate measures indicated that demographic and high school preparation variables were the most beneficial in predicting success among student-athletes. Perhaps the most significant finding was that when included in the regression analysis with other high school preparation variables, SAT scores were not significantly related to graduation. The most significant variables were high school grade point average and the number of college preparatory math classes taken.
Keywords: academic predictors; academic support; math; academic performance